2018
DOI: 10.3390/polym11010016
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Washable Smart Textiles with Photothermal and Antibacterial Activities from Nanocomposite Fibers of Conjugated Polymer Nanoparticles and Polyacrylonitrile

Abstract: Smart textiles based on conjugated polymers have been highlighted as promising fabrics that can intelligently respond to environmental stimuli based on the electrical properties of polymer semiconductors. However, there has been limited interest in the photothermal properties of conjugated polymers that can be applied to smart textiles. We prepared nanoparticles by assembling a conjugated polymer with a fatty acid via an emulsion process and nanocomposite fibers by distributing the conjugated polymer nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…The need to study the impact of the washing process on textronics was underlined back in 2004 [4] and it is all the more relevant that smart textiles are on the edge of being commercialized [5]. However, few research papers have tackled this particular issue until now, although it can be noted that the washability aspect of recent developments is more clearly taken into account [6][7][8]. However, as noted by Zaman et al [9], there is a lack of standardizations on the washing process to be followed, the detergent to use and the number of washing cycles required to claim that a smart textile is really washable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to study the impact of the washing process on textronics was underlined back in 2004 [4] and it is all the more relevant that smart textiles are on the edge of being commercialized [5]. However, few research papers have tackled this particular issue until now, although it can be noted that the washability aspect of recent developments is more clearly taken into account [6][7][8]. However, as noted by Zaman et al [9], there is a lack of standardizations on the washing process to be followed, the detergent to use and the number of washing cycles required to claim that a smart textile is really washable.…”
Section: Introductionmentioning
confidence: 99%
“…However, as noted by Zaman et al [9], there is a lack of standardizations on the washing process to be followed, the detergent to use and the number of washing cycles required to claim that a smart textile is really washable. As a result, among the few studies that can be found in the literature on the subject, smart garment prototypes are claimed washable according to various standards: ISO 6330:2000 [10,11], ISO 105-C01 [12] or ISO15797 [11], method 61-2010 of the American Association of Textile Chemists and Colorists (AATCC, Table 1) [6]. Hence, the utmost importance of the current work of research groups to provide a consensus standard with normalized tests for assessing the launderability and reliability of e-textiles, which is complex due to their heterogeneous nature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CPNs can be widely examined as photothermal therapeutic agents, photoacoustic probes, and photocatalysts in aqueous-based applications. In addition, they could be incorporated into functional fibers via a solution spinning process utilizing DMF and DMSO [101,102]. Another advantage of CPNs is that they can present optoelectronic properties similar to those of their bulk or thin-film states.…”
Section: Photothermal Heating By Conjugated Polymer Nanomaterials (Cpns)mentioning
confidence: 99%
“…In comparison, conjugated polymer backbones inside CPNs are isolated from the surrounding polar media, and thus, their optoelectronic properties can be significantly preserved. In addition, the stacking of π-conjugated backbones as in films of conjugated polymers with ordered assembly structures is possible, resulting in a bathochromic shift in their absorption spectra by intermolecular π-electron delocalization, as shown in the absorption spectra of poly [2,6- [102]. As a result, the NIR absorption and heat emission properties of CPNs are significantly enhanced.…”
Section: Photothermal Heating By Conjugated Polymer Nanomaterials (Cpns)mentioning
confidence: 99%
See 1 more Smart Citation